PEMAKNAAN FILSAFAT NILAI SANTRI DALAM KEHIDUPAN BERMASYARAKAT: (STUDI DI PONDOK PESANTREN HIDAYATUL MUBTADI-IEN NGUNUT TULUNGAGUNG) - RIDWAN, MUHAMMAD FAUZI; Izzatul Amalina; Riyanto, Riyanto (STAI KH. Muhammad Ali Shodiq, 2023)
Abstract As an educational institution, pesantren certainly have unique values compared to other educational institutions. This article aims to describe the meaning and implementation of the value philosophy of santri at Hidayatul Mubtadi-ien Islamic Boarding School (PPHM) Ngunut Tulungagung in social life. The author takes the subject of Ngunut boarding school students who have lived in society. This article uses a qualitative approach in the form of phenomenology. The data collection methods used include observation, interviews and documentation. Researchers use descriptive analysis which aims to explain aspects relevant to the observed phenomenon. Furthermore, researchers use triangulation techniques to test the validity of the data obtained. The results of this study that: Ngunut hut students interpret value philosophy as uswah or exemplary value, discipline value, akhlakul karimah value and togetherness value. The implementation of the value philosophy of the Ngunut boarding school students in community life by being tolerant, morally good, independent in meeting the economic needs of the family, being uswah in the community and the next generation of religious leaders in the community. Keywords: Meaning, Value Philosophy, Santri, Pesantren, Community Life